2020
DOI: 10.3201/eid2604.190435
|View full text |Cite
|
Sign up to set email alerts
|

Severe Dengue Epidemic, Sri Lanka, 2017

Abstract: G lobal incidence of dengue has increased 7-fold, from 8.3 million cases in 1990 to >58.4 million in 2013 (1). Currently, ≈390 million new infections occur annually in 128 dengue-endemic countries (2). Worldwide, ≈14,000-20,000 dengue-related deaths occur each year (1,2). In dengue-endemic countries, Aedes (Stegomyia) aegypti and Ae. (Stegomyia) albopictus mosquito vectors transmit the disease. Sri Lanka, a tropical island in the Indian Ocean (population 21 million) (3), has reported dengue cases since the 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 34 publications
3
61
0
1
Order By: Relevance
“…From 2010 to 2016, dengue became a major public health problem, with a steady increase in cases from 28,473 to 55,150 cases in 2011 and 2016 respectively [ 10 ]. In 2017, Sri Lanka reported 186,101 dengue cases and 440 deaths (case fatality rate 0.24%), the highest number of cases reported in one year since dengue was incorporated into the integrated disease surveillance system as a notifiable disease in 1996 [ 11 ]. In 2019, a total of 104,695 cases with 157 deaths (case fatality rate 0.15%) were reported [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…From 2010 to 2016, dengue became a major public health problem, with a steady increase in cases from 28,473 to 55,150 cases in 2011 and 2016 respectively [ 10 ]. In 2017, Sri Lanka reported 186,101 dengue cases and 440 deaths (case fatality rate 0.24%), the highest number of cases reported in one year since dengue was incorporated into the integrated disease surveillance system as a notifiable disease in 1996 [ 11 ]. In 2019, a total of 104,695 cases with 157 deaths (case fatality rate 0.15%) were reported [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…DENV-2 and DENV-3 were not detected from the year 2009 to mid-2016, although the predominant circulating serotypes prior to the year 2009 were DENV-2 and DENV-3 [ 10 12 ]. The largest reported epidemic of dengue was seen in 2017, with a total number of 186,101 cases being notified with 440 deaths, which coincided with the reemergence of DENV-2 [ 13 ]. Although fewer cases were reported in 2018 (51,659 cases) compared to 2017, there was again another surge in 2019, with 105,049 cases reported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, an unprecedented magnitude of severe dengue epidemic occurred in Sri Lanka and cosmopolitan genotype of DENV-2 was dominant in the most affected district (19). In our previous study on this outbreak 14, we reported the detection of cosmopolitan genotype of DENV-2 (74%) and genotype I of DENV-4 (1%).…”
Section: Discussionmentioning
confidence: 91%